KONSUMSI REBUSAN DAUN SIRIH MERAH EFEKTIF TERHADAP PERUBAHAN KADAR GULA DARAH PENDERITA DIABETES MELLITUS - Yesi Septina Wati; Ririn Muthia Zukhra; Ika Permanasari (STIKes Al-Insyirah Pekanbaru, 2020)
The treatment for patient with diabetes mellitus can be applied by non pharmalogical therapies. The purpose of this study was to determine the effect of red betel lleaf decoction on changes in blood sugar levels in patients with diabetes mellitus in rw 26 of rejosari sub-district of tenayan raya pekanbaru cirty. This type of research is quasy experimental. The study sample was all diabetes mellitus patients in Rw- 26, rejosari village, tenayan raya district, pekanbaru city, 15 people, the results showed that the p value of blood level was 0.001 (p< 0.005). this shows that there is a significant influence on the consumption of red betel leaf stew on blood levels. It is expected for Rw- 26 kelurahan Rejo sari to use betel leaf as a non- pharmacological therapy in the treatment of diabetes.